The importance of employees’ engagement on the organizational success - Costa, L.; Loureiro, S. M. C. (Journal of Promotion Management, 2019)
This study intends to analyze the influence of employees’ engagement on the organizational success. The results demonstrate that organizations are aware of the importance of retain and create happiness at work and are starting to create an internal experience for their workforce. When employees are happier at work, they tend to take part of the ownership of their organizations. Employees are more focused on people and the value that they can add to the products designed, created, and delivered by them. All these investment on internal world is feeding a better consumer experience as the quality standards are getting higher.